2018
DOI: 10.1111/ctr.13454
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of high‐intensity statin therapy in heart transplant patients receiving immunosuppression with tacrolimus

Abstract: BackgroundFollowing heart transplantation (HT), HMG CoA reductase inhibitors (statins) have been shown to reduce total and low‐density lipoprotein (LDL) cholesterol, development of cardiac allograft vasculopathy (CAV), and mortality. Studies in HT patients have demonstrated the safety of low/moderate intensity statins; however, little data exist using high‐intensity (HI) statins. The study aim was to evaluate the safety and efficacy of HI statins in HT recipients receiving tacrolimus.MethodsThis single‐center,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…The 16 case reports, 12 published as case report manuscripts and four published as editorial briefs, and two case series are charted in Table 1 8–25 . The three original research manuscripts, two retrospective observational cohort studies and one case‐control study, are charted in Table 2 26–28 . No randomized controlled studies were obtained from the literature search.…”
Section: Resultsmentioning
confidence: 99%
“…The 16 case reports, 12 published as case report manuscripts and four published as editorial briefs, and two case series are charted in Table 1 8–25 . The three original research manuscripts, two retrospective observational cohort studies and one case‐control study, are charted in Table 2 26–28 . No randomized controlled studies were obtained from the literature search.…”
Section: Resultsmentioning
confidence: 99%
“…29 Recently, a retrospective analysis was completed of 24 heart transplant patients on tacrolimus who were transitioned to high-intensity statins (atorvastatin n = 23 and rosuvastatin n = 1) during posttransplant follow-up. 30 The primary aim of this study was to investigate the incidence of adverse effects such as myopathy, hepatotoxicity, and rhabdomyolysis. Patients demonstrated tolerance of low-moderate statins for 6 months prior to conversion to high-intensity statin.…”
Section: Statin Safety and Adverse Events With Tacrolimusmentioning
confidence: 99%
“…Some transplant centers even include the use of statins preemptively as part of the standard posttransplant medication regimen regardless if hyperlipidemia was not present pretransplant, as recommended by international guidelines. 12,30 Another consideration is that transplant candidates may also have preexisting CVD, necessitating use of statins posttransplant. Statins have an important role in this population, and when used at the doses necessary to reduce LDL, they can provide significant benefit.…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%
“…A recent Cochrane review identified four studies on the use of statin therapy in kidney transplant patients to minimise cardiovascular mortality [67], all reporting a non-statistically significant reduction in cardiovascular mortality. This was likely due to the low statin doses used (10 mg daily equivalent simvastatin), compared to the higher intensity statin therapy used to manage CAV (20 mg daily equivalent simvastatin) [68]. This point is further illustrated by a more recent study which revealed a dose-dependent benefit of statins in survival among kidney transplant patients [69].…”
mentioning
confidence: 99%